Canadian Music Teachers’ Burnout and Resilience Through the Second Wave of the COVID-19 Pandemic - Laidlaw, Jordan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2023)
The COVID-19 pandemic globally impacted teachers’ wellbeing as they adjusted their practices to accommodate physical distancing, online learning, and hybrid models. Coinciding these changes, music teachers were impacted by local health regulations and school divisional policy revisions prohibiting singing and playing wind instruments indoors. Consequently, music teachers were required to abruptly change their practice, were displaced to alternative locations (e.g., gymnasiums), and/or were required to use travelling carts to teach. Research into the impacts that COVID-19 policy changes had on school music remains limited in Canadian contexts. To provide insight into this phenomenon, the research question was formulated: “What are music teachers’ perspectives on how the COVID-19 pandemic impacted their sense of wellbeing?” To facilitate the inquiry, a mixed-methods approach was utilized via an online attitudinal survey, a questionnaire, and focus group discussions. In total, 218 music teachers across Manitoba, Canada participated in the online survey and completed the questionnaire while 21 music teachers participated in focus group discussions. Findings demonstrated that music teachers experienced significantly strenuous working conditions throughout the pandemic, resulting in many teachers considering early retirement or resignation. Despite these challenges, music teachers demonstrated considerable resilience as they navigated the educational landscape in the province.